Zeolites and zeolite imidazole frameworks in pharmacy (review) - E. O. Bakhrushina; N. O. Belyavsky; V. N. Kuzina; A. I. Khodenok; N. B. Demina; G. V. Ramenskaya (Разработка и регистрация лекарственных средств, 2025)
Introduction. One example of new polymers for target delivery systems are zeolites (ZEO) and zeolite imidazole frameworks (ZIF). ZEO are actively used in industry, ecology, pharmacy and biomedicine, having high porosity, adsorption capacity and physico-chemical stability. ZIF, as a type of metal-organic framework, are characterized by high thermal and chemical resistance, biocompatibility and adjustable porosity, which makes them promising for drug delivery. Both polymers, due to their properties, open up new opportunities for the creation of targeted drugs with prolonged action and minimal side effects. The purpose of this review is to characterize ZEO and ZIF as promising polymers for targeted delivery systems and to consider their basic properties.Text. The article discusses the structure and methods of analysis of zeolites and zeolite imidazole frameworks, methods of their synthesis, mechanism of action, and applications of polymers as directed delivery systems.Conclusion. The review shows that the chemical and physical properties of ZEO and ZIF polymers make it possible to develop effective targeted drug delivery systems used in oncology, ophthalmology, dentistry and orthopedics. Low cytotoxicity, regulated polymer pore loading and the effectiveness of intracellular targeting confirm the prospects of using ZEO and ZIF in medicine.